2015
DOI: 10.4490/algae.2015.30.3.197
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and phylogenetic position of a freshwater Prasiola species (Prasiolales, Chlorophyta) in Korea

Abstract: The genus of leafy green algae, Prasiola Meneghini, includes marine, terrestrial, and freshwater species. A total of 11 species and one variety have been identified in China, Korea, and Japan. In Korea, Prasiola formosana var. coreana has been reported in Muncheon, North Korea, while a different type of Prasiola species has been reported in South Korea. The South Korean species has been found growing along a small stream originating from Chodanggul Cave, a limestone cave in Samcheok, Gangwon Province. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Kim et al . () recently identified P. japonica in Korea, and synonymized P. yunnanica with P. japonica , based on identical rbc L, tuf A and psa B sequence data among specimens of both species. Our data support their conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al . () recently identified P. japonica in Korea, and synonymized P. yunnanica with P. japonica , based on identical rbc L, tuf A and psa B sequence data among specimens of both species. Our data support their conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Cellular and ultrastructural characters and molecular analysis support the idea that Prasiolales is a monophyletic well-defi ned order and has a relationship with the Trebouxiophyceae, Chlorophyta (Garbary & Hill, 2017;Heesch et al, 2016;Moniz et al, 2012;Pang et al, 2021). A total of 37 species have been reported in the green algal genus Prasiola (Guiry & Guiry, 2022), with as many as 14 documented as freshwater organisms (Moniz et al, 2012), and 11 of which are reported in Asia (Kim et al, 2015;Pang et al, 2021). The genus is characterized by a monostromatic, foliose blade; a stellate chloroplast with a central pyrenoid; and a unique type of life history, where diploid thalli can form either diploid spores or haploid gametes within the thallus resulting in a haploid apex and diploid base (Lee, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The genus is characterized by a monostromatic, foliose blade; a stellate chloroplast with a central pyrenoid; and a unique type of life history, where diploid thalli can form either diploid spores or haploid gametes within the thallus resulting in a haploid apex and diploid base (Lee, 2008). Species of Prasiolia are macroscopic, benthic green algae and distributed in freshwater (Rodríguez & Jiménez, 2005;Kim et al, 2015), marine (Moniz et al, 2012), and terrestrial habitats (Rindi et al, 1999(Rindi et al, , 2004. They seem to be notable primary producers specifi cally in extremely harsh Arctic, Antarctic, and subarctic environments with very low temperature, freeze and thaw cycles, severe wind events, nutrient limitations, low humidity, and desiccation (Rindi et al, 1999, Sherwood et al, 2000Heesch et al, 2016;Klochkova et al, 2017;Broady, 1989;McKnight et al, 1998, Kováčik & Pereira, 2001, Carvalho et al, 2017Jacob et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 36 species of the genus Prasiola have been reported, of which 14 are freshwater species [2]. In Korea, Park et al found a Prasiola species in Samcheok, Gangwon-do, in 1970 [3], and this was later identified as P. japonica, distributed in Korea and Japan as traditionally edible algae [4]. Pharmaceutical benefits such as antioxidant, anti-inflammatory, and skin-protective effects have been confirmed in various in vitro and in vivo models [5][6][7].…”
Section: Introductionmentioning
confidence: 99%